Reliability, and Convergent and Discriminant Validity of Gaming Disorder Scales: A Meta-Analysis - Yoon, Seowon; Yang, Yeji; Ro, Eunbin; Ahn, Woo-Young; Kim, Jueun; Shin, Suk-Ho; Chey, Jeanyung; Choi, Kee-Hong (Frontiers in Psychology, 2021)
Background: An association between gaming disorder (GD) and the symptoms of common mental disorders is unraveled yet. In this preregistered study, we quantitatively synthesized reliability, convergent and discriminant validity of GD scales to examine association between GD and other constructs. Methods: Five representative GD instruments (GAS-7, AICA, IGDT-10, Lemmens IGD-9, and IGDS9-SF) were chosen based on recommendations by King et al. (2020) to conduct correlation meta-analyses and reliability generalization. A systematic literature search was conducted through Pubmed, Proquest, Embase, and Google Scholar to identify studies that reported information on either reliability or correlation with related variables. 2,124 studies were full-text assessed as of October 2020, and 184 were quantitatively synthesized. Conventional Hedges two-level meta-analytic method was utilized. Results: The result of reliability generalization reported a mean coefficient alpha of 0.86 (95% CI = 0.85 - 0.87) and a mean test-retest estimate of .86 (95% CI = 0.81 – 0.89). Estimated effect sizes of correlation between GD and the variables were as follows: .33 with depression (k = 45; number of effect sizes), .29 with anxiety (k = 37), .30 with aggression (k = 19), -.22 with quality of life (k = 18), .29 with loneliness (k = 18), .56 with internet addiction (k = 20), and .40 with game playtime (k = 53) respectively. The result of moderator analyses, funnel and forest plots, and publication bias analyses were also presented. Discussion and conclusions: All five GD instruments have good internal consistency and test-retest reliability. Relatively few studies reported the test-retest reliability. The result of correlation meta-analysis revealed that GD scores were only moderately associated with game playtime. Common psychological problems such as depression and anxiety were found to have a slightly smaller association with GD than the gaming behavior. GD scores were strongly correlated with internet addiction. Further studies should adopt a rigorous methodological procedure to unravel the bidirectional relationship between GD and other psychopathologies. Limitations: The current study did not include grey literature. The representativeness of the five tools included in the current study could be questioned. High heterogeneity is another limitation of the study.